Representation of the Indonesia Government in Handling COVID-19 Case on Tempo Magazine Cover - Anggraeni, Yulia; Soemantri, Ypsi Soeria; Indrayani, Lia Maulia (e-Journal of Linguistics; Vol 15 No 1 (2021): ejl-JanuaryDO - 10.24843/e-jl.2021.v15.i01.p02, 2020)
The World Health Organization (WHO) officially announced the COVID-19 outbreak as a global pandemic. The efforts made by the government in handling this case are often discussed. Various media provide news about COVID-19. One of the media that provides news about the government's efforts in handling the COVID-19 is Tempo Magazine. In several editions, Tempo Magazine made COVID-19 topics as a magazine cover. The cover is the data in this study. This study aims to see how the Indonesian government is represented by Tempo Magazine in terms of handling COVID-19 using the action of signs theory by Charles Sanders Peirce. The results of this study are; (1) Tempo Magazine represents the government’s difficulty to face a pandemic and the coordination between the president and Minister of Health is not good. This makes people panic; (2) The Tempo Magazine sees that the government only makes a small effort in terms of fighting coronavirus in Indonesia and does not have good strategies to face it; (3) Tempo Magazine seems to doubt the new normal proclaimed by the government.